2019
DOI: 10.1007/978-3-030-32497-1_29
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Eco-Design Methods Using TRIZ Tools: the Case of ECOFAIRE

Abstract: Green design is a relevant research topic because of the need of powerful and confirmed systematic methods that can support companies in their efforts to develop green products within acceptable time and costs.TRIZ, as a theory of invention problem-solving has proven its effectiveness in stimulating designer's creativity in several areas. Therefore, the main research question we address in this research is the following: how can TRIZ tools enhance the ideality of green-design methods?This paper presents an exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Many papers provide a single case study about a specific application field (e.g. Moussa et al, 2019;Santagata et al, 2020); others consider more case studies but generally no more than ten, except for Spreafico (2021). The most difficult studies to compare are the ones they propose a single case study and a single design strategy (e.g.…”
Section: State Of the Artmentioning
confidence: 99%
“…Many papers provide a single case study about a specific application field (e.g. Moussa et al, 2019;Santagata et al, 2020); others consider more case studies but generally no more than ten, except for Spreafico (2021). The most difficult studies to compare are the ones they propose a single case study and a single design strategy (e.g.…”
Section: State Of the Artmentioning
confidence: 99%
“…TRIZ and BioTRIZ are powerful tools that can effectively stimulate product creativity in green design [16,17]. Accordingly, it is important to establish a correlation table between environmental efficiency elements and engineering parameters (EP) [18], such as green materials and green energy.…”
Section: Renewmentioning
confidence: 99%
“…If the environmental aspect is not considered during the resolution phase of our problems, the result will be catastrophic (Huppes and Ishikawa 2007). The need of an effective systematic methodology has been developed in this paper, it shows that many approaches have been presented in the literature, however green design remains a relevant research topic because of the lack of powerful and confirmed systematic methods that can support companies in their efforts to develop green products within acceptable time and costs (Ben Moussa et al 2019).…”
Section: Introductionmentioning
confidence: 99%